Purtscher-like Retinopathy Associated with Systemic Lupus Erythematosus - Paradee Kunavisarut (2018)
© 2016 Taylor & Francis Group, LLC. Purpose: To report on clinical manifestations of Purtscher-like retinopathy (PLR) associated with systemic lupus erythematosus (SLE) and visual outcomes. Methods: We performed a retrospective cohort study of 11 patients (21 affected eyes) with PLR in SLE. Results: All patients were treated with systemic corticosteroids ± immunosuppressive agents. Ocular therapy included intravitreal injections with bevacizumab in 18/21 eyes and posterior sub-Tenon injections with triamcinolone acetonide 13/21 eyes. Panretinal photocoagulation (PRP) was performed in 19/21 eyes and pars plana vitrectomy was required in 5/21 eyes. Visual improvement was found at follow-up of 3 and 6 months (p = 0.05). Poor visual outcome was associated with presence of neovascularizations at onset (p = 0.009), development of vitreous hemorrhage during PRP (p = 0.015), and active status of SLE after onset of PLR (p = 0.029). Conclusions: PLR might manifest as a devastating complication of SLE. We recommend treating any systemic activity of SLE and starting an early ocular treatment.